Spatiotemporal patterns of sediment transport rate and beach-ocean profile for multi-hazard risk management - Khorram, Saeed; Ergil, Mustafa (Springer, 2018)
Many parameters, interacting differently in time and space, affect a long-shore hydrological and marine ecosystem model, and the water resource management advancement is highly affected by these interactions. Sediment transport in coastal regions is due to interactions between various land forms and different complicated physical processes. What determines coast to storm vulnerability, public/private land ownership legal boundaries, and beach extent that can be used for recreation/habitat is the shape of BOP (beach-ocean profile). This paper addresses an approach that requires a disorder power index (entropy power) for the analyses of spatiotemporal patterns and reports, on the basis of a beach area case study, the suitability of the index for the analyses of the hydrological/marine ecosystem components. The approach uses the 1970-2015 monthly data of six Makran ocean beach sections and investigates such variables as wave high, wind speed, and total beach sediment transport rates (TBSTR) spatiotemporal patterns each of which depends on time and plays an important part in terrestrial hydrological studies. Although these variables often show meaningful spatiotemporal variability, their combined performance is hard to explain. In the framework of this context, using entropy-power index exhibits important signals that help the assessment of water resources and provides a clear understanding of the interactions among hydrological parameters at such large scales as the beach area.
Keywords: Coastline Zone; Wave high; Wind speed; Entropy theory; Spatiotemporal; Beach-ocean profile